Sosialisasi Penggunaan ATM Beras Bagi Penduduk di Kelurahan Borongloe - Ida Rachmaniar Sahali; Andani Achmad .; Rhiza S. Sadjad .; Faizal A. Samman .; Ansar Suyuti .; Salama Manjang .; Dewiani .; Muh. Anshar .; Gassing .; Yusran .; Ardiaty Arief .; Muh. Bachtiar Nappu .; Fighi S. Permadi . (Faculty of Engineering UNHAS, 2022)
The government has a rice distribution program as assistance for low-income communities to support food security. The distribution of rice has several problems including the wrong size, allocation, price, distribution time, and at the time of distribution it is vulnerable to crowds. Even though in the midst of the Covid-19 Pandemic, one way to prevent the transmission of the virus is to avoid crowds. For this reason, a Rice ATM is designed that can manage rice distribution using technology. Rice ATMs can also be used to distribute zakat or rice alms at Baznas or in mosques. Therefore, this service activity aims to socialize the Rice ATM and the procedures for its use to residents in Borongloe Village, Gowa Regency. The method begins with implementing ATM Rice then conducting outreach activities and giving questionnaires to determine the level of knowledge of the participants. From giving the questionnaire before the socialization activity, it was found that the majority of participants did not know about ATM Rice and after participating in the socialization activity, the majority of participants considered the use of ATM Rice to make it easier in terms of service.